Histologic, metabolomic, and transcriptomic differences in fir trees from a peri‐urban forest under chronic ozone exposure - Reyes‐Galindo, Verónica; Jaramillo‐Correa, Juan P.; Shishkova, Svetlana; Sandoval‐Zapotitla, Estela; Flores‐Ortiz, César Mateo; Piñero, Daniel; Spurgin, Lewis G.; Martin, Claudia A.; Torres‐Jardón, Ricardo; Zamora‐Callejas, Claudio; Mastretta‐Yanes, Alicia (Ecology and evolution, 2024)
Urbanization modifies ecosystem conditions and evolutionary processes. This includes air pollution, mostly as tropospheric ozone (O3), which contributes to the decline of urban and peri‐urban forests. A notable case are fir (Abies religiosa) forests in the peripheral mountains southwest of Mexico City, which have been severely affected by O3 pollution since the 1970s. Interestingly, some young individuals exhibiting minimal O3—related damage have been observed within a zone of significant O3 exposure. Using this setting as a natural experiment, we compared asymptomatic and symptomatic individuals of similar age (≤15 years old; n = 10) using histologic, metabolomic, and transcriptomic approaches. Plants were sampled during days of high (170 ppb) and moderate (87 ppb) O3 concentration. Given that there have been reforestation efforts in the region, with plants from different source populations, we first confirmed that all analyzed individuals clustered within the local genetic group when compared to a species‐wide panel (Admixture analysis with ~1.5K SNPs). We observed thicker epidermis and more collapsed cells in the palisade parenchyma of needles from symptomatic individuals than from their asymptomatic counterparts, with differences increasing with needle age. Furthermore, symptomatic individuals exhibited lower concentrations of various terpenes (ß‐pinene, ß‐caryophylene oxide, α‐caryophylene, and ß‐α‐cubebene) than asymptomatic trees, as evidenced through GC–MS. Finally, transcriptomic analyses revealed differential expression for 13 genes related to carbohydrate metabolism, plant defense, and gene regulation. Our results indicate a rapid and contrasting phenotypic response among trees, likely influenced by standing genetic variation and/or plastic mechanisms. They open the door to future evolutionary studies for understanding how O3 tolerance develops in urban environments, and how this knowledge could contribute to forest restoration. RESUMEN La urbanización altera tanto las condiciones del ecosistema como los procesos evolutivos, siendo la contaminación del aire, principalmente el ozono troposférico (O3), un factor que contribuye al declive de los bosques urbanos y periurbanos. Un ejemplo destacado son los bosques de oyamel (Abies religiosa) en las montañas periféricas al suroeste de la Ciudad de México, que han sufrido graves afectaciones por la contaminación de O3 desde la década de 1970. Resulta curioso observar que algunos individuos jóvenes presentan un daño mínimo relacionado con el O3 dentro de zonas con una exposición significativa a este contaminante. Aprovechando este entorno como un experimento natural, hemos comparado individuos asintomáticos y sintomáticos de edad similar (≤15 años; n = 10) mediante enfoques histológicos, metabolómicos y transcriptómicos. Las muestras de plantas se recolectaron durante días con concentraciones altas (170 ppb) y moderadas (87 ppb) de O3. Dado que se han llevado a cabo esfuerzos de reforestación en la región con plantas de diferentes poblaciones, primero confirmamos que todos los individuos analizados se organizaron dentro del grupo genético local en comparación con un amplio panel poblacional de esta misma especie (Análisis de Admixture con ~1.5 K SNPs). Observamos una epidermis más gruesa y más células colapsadas en el parénquima en empalizada de las agujas de los individuos sintomáticos que de sus contrapartes asintomáticas, y estas diferencias aumentaban con la edad de la aguja. Además, los individuos sintomáticos exhibieron concentraciones más bajas de varios terpenos (ß‐pineno, óxido de ß‐cariofileno, α‐cariofileno y ß‐α‐cubebeno) que los árboles asintomáticos, según se evidenció mediante GC–MS. Por último, los análisis transcriptómicos revelaron una expresión diferencial para trece genes relacionados con el metabolismo de carbohidratos, la defensa de plantas y la regulación génica. Nuestros resultados indican una respuesta fenotípica rápida y contrastante entre los árboles, probablemente influenciada por la variación genética presente y/o mecanismos plásticos. Estos hallazgos abren la puerta a futuros estudios evolutivos para comprender cómo se desarrolla la tolerancia al O3 en entornos urbanos y cómo este conocimiento podría contribuir a la restauración forestal. Urbanization alters ecosystems and evolutionary processes. Processes like air pollution by tropospheric ozone contribute to the decline of urban and peri‐urban ecosystems, such as Abies religiosa forests in the peripheral mountains southwest of Mexico City. Despite ozone exposure, some young individuals present minimal damage, suggesting contrasting phenotypic responses that may be influenced by genetic variations and/or plastic mechanisms, opening new perspectives for evolutionary studies on ozone tolerance and forest restoration.